Self-assembled nanoparticles of acetylated cashew gum: Characterization and evaluation as potential drug carrier. (6th March 2015) - Pitombeira, Nadia A.O.; Veras Neto, José Guilherme; Silva, Durcilene A.; Feitosa, Judith P.A.; Paula, Haroldo C.B.; de Paula, Regina C.M.
Highlights: Acetylated cashew gum was successfully synthesized. Self-assembled nanoparticles were produced by the dialysis method. Spherical nanoparticle with unimodal particle size distributions were observed. Controlled indomethacin release was observed for up to 72 h. Abstract: Acetylated cashew gum (ACG) was synthesized and self-assembled nanoparticles were obtained through the dialysis of an organic solution (DMSO) against a non-solvent (water). The ACG was characterized by infrared spectroscopy. The degree of substitution was 2.8 as determined by NMR spectroscopy. The physicochemical properties of the self-assembled nanoparticles in aqueous media were characterized by DLS, SEM and fluorescence spectroscopy. The mean diameter of the self-assembled nanoparticles obtained was 179 nm and the critical aggregation concentration (CAC) in water was 2.1 × 10 −3  g/L. Indomethacin (IND) was used as a hydrophobic model drug and was incorporated into the hydrophobized polysaccharide. Both loaded and unloaded nanoparticles were found to be spherical with diameters in the ranges of 70–170 nm and 108–314 nm (determined by SEM), respectively. Controlled drug release was observed for up to 72 h.